The Relationship Between Work Environment and Work-Life Balance on Employee Performance - Salsabilla, Nezia; Margareta, Silva; Alwi, Muhamad (Eduvest - Journal of Universal Studies, 2025)
The purpose of this study is to examine how work-life balance and the workplace affect employee performance.  The methodology employed in this study is quantitative descriptive correlation research.  Every one of PT. Siraj Badawi's 102 workers  The research population, Enough Rupiah, was chosen through the use of a direct random sample technique.  Data is obtained through questionnaires on work atmosphere, work-life balance, and employee performance.  The data in this study was analyzed using multiple linear regression analysis.  The work environment of PT. Siraj Badawi has a significant impact on employee performance, according to the findings of the Multiple Linear Regression analysis using the t test and the F test. Employee performance at PT. Siraj Badawi is significantly impacted by work-life balance.  Employee performance at PT. Siraj Badawi is significantly impacted by the work environment and work-life balance.  Employee performance at PT. Siraj Badawi is impacted by the workplace culture and work-life balance.  41% of Rupiah is sufficient.